Tailored exercise with an innovative mechanical device: Effects on cervical-dorsal rachis - Messa, L. V.; Biffi, A.; Fernando, F.; Ginanneschi, F.; Rossi, A. (Journal of Functional Morphology and Kinesiology, 2016)
Trapezius muscle has a fundamental role in cervico-dorsal pain and posture. Often, in movements involving trapezius, the predominant activity is carried out by the upper trapezius, and many times this may be a risk factor for the integrity of the cervico-dorsal structures. To investigate the effects of physical exercise with the new device called the "Angel`s Wings" on a sample of different professionals. We enrolled 15 volunteers for electromyography (EMG) data, which was collected during the physical performance; 3 volunteers for magnetic resonance imaging (MRI) data, collected before and after a training period; and 73 workers of Ferrari S.p.A. and the Scuderia Ferrari racing team division for a visual analogue scale (VAS) pain score, collected before and after one session of training. EMG shows a decoupling of upper and lower trapezius activity; MRI shows a realignment of cervical-dorsal rachis after one month of training; VAS pain score significantly decreased after the physical exercise with the "Angel`s Wings". Results show that the use of the "Angel`s Wings" is applicable to counteract and decrease the neck pain by a decontraction of the upper trapezius and correct postural defects of the cervico-dorsal column.